ON A PROPERTY OF NORMING CONSTANTS OF STURM–LIOUVILLE PROBLEM - Asatryan, Yu.A.; Harutyunyan, T.N. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2014)
A connection, which shows the dependence of norming constants on boundary conditions, was found using the Gelfand–Levitan method for the solution of inverse Sturm–Liouville problem.